2019
DOI: 10.1038/s41598-019-51194-w
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of dietary aryl hydrocarbon receptor ligands alters microbiota composition and function

Abstract: The intestinal microbiota is critical for maintaining homeostasis. Dysbiosis, an imbalance in the microbial community, contributes to the susceptibility of several diseases. Many factors are known to influence gut microbial composition, including diet. We have previously shown that fecal immunoglobulin (Ig) A levels are decreased in mice fed a diet free of aryl hydrocarbon receptor (AhR) ligands. Here, we hypothesize this IgA decrease is secondary to diet-induced dysbiosis. We assigned mice to a conventional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 57 publications
(67 reference statements)
1
31
1
Order By: Relevance
“…33 Our results suggest that indole or its derivatives are, in some measure, responsible for the rescue of the anxiety-like behavior in our model. We observed previously reported indole negative associations in taxa such as Erysipelotrichaceae 24 in IBS+A mice that were restored by S. bou. Moreover, predicted metabolomic profile indicated that IBS+A mice treated with S. bou had indeed higher number of bacterial genes implicated in indole alkaloid biosynthesis compared with IBS+A mice receiving water ( Figure 5A), also suggesting higher indole levels.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…33 Our results suggest that indole or its derivatives are, in some measure, responsible for the rescue of the anxiety-like behavior in our model. We observed previously reported indole negative associations in taxa such as Erysipelotrichaceae 24 in IBS+A mice that were restored by S. bou. Moreover, predicted metabolomic profile indicated that IBS+A mice treated with S. bou had indeed higher number of bacterial genes implicated in indole alkaloid biosynthesis compared with IBS+A mice receiving water ( Figure 5A), also suggesting higher indole levels.…”
Section: Discussionmentioning
confidence: 63%
“…Taxa expanded in IBS+A mice and decreased by S. bou, such as Erysipelotrichaceae, have been shown to be affected by dietary indole levels. 24 PICRUSt analysis indicated that IBS+A mice treated with S. bou had over 20-fold (p = 0.01) higher number of bacterial genes implicated in indole alkaloid biosynthesis compared with IBS+A mice receiving water ( Figure 5A), suggesting higher levels of indole.…”
Section: S Bou Increases Microbial Indole Production In Vitromentioning
confidence: 99%
“…AHR ligands include tryptophan metabolites derived from microbiota and dietary macronutrients. The activation of the AHR signaling pathway is important for maintaining gut health including a direct effect on mucosal immunity [74]. For example, intestinal AHR signaling is important for intestinal crypt stem cell differentiation [75].…”
Section: Polyamines Ahr Ligands and Gut Homeostasismentioning
confidence: 99%
“…In comparison to the diverse microbiota of mice reared on conventional grain-based chow, the immune phenotype of the microbiome of mice fed purified, phytochemical-free diets (often termed AHR ligand-free diets) is changed in a manner similar to that seen in AHR-deficient animals [ 28 , 112 , 113 ]. Like the AHR-deficient mice, animals fed purified, phytochemical-free diets exhibit enhanced susceptibility to severe colitis [ 113 , 114 , 115 ].…”
Section: The Mechanism(s) By Which Ficz Il-22 and Butyrate Promotmentioning
confidence: 99%